Evaluation of the Right to Food with Food System Approach at the Provincial Level in Indonesia - Akber Maulad; Drajat Martianto; Ikeu Ekayanti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2022)
Background: The right to food is one of the human rights that must be protected and fulfilled. Inequality in priorities on food and nutrition security development causes a sharp distinction among provinces regarding food security achievement. Currently, methods for evaluating the right to food at the provincial level are not yet available. Objectives: This study aims to analyze the right to food at the provincial level in Indonesia with a food system approach (food availability, food accessibility, and food utilization) using structural, process, and outcome indicators. Methods: This study was a cross-sectional study using secondary data from 34 provinces in Indonesia. The data consist of regulations, programs, and the government's performance achievements. There were five data analysis stages: identification, selection, assessment indicators, provincial rankings provision, and the characteristics based on cluster analysis. Results: Based on the evaluation of 36 selected indicators of the right to food, only three provinces were included in the high category, twenty-five provinces in the medium category, and six provinces in the low category. Central Java had the highest level of the right to food, while West Papua had the lowest level. Non-hierarchical clustering with K-Means methods was further applied to analyze the right to food and later divided into five clusters. The first until the third cluster was categorized as medium level, while the fourth and fifth clusters were categorized as low. Conclusions: The right to food in western part of Indonesia had better than the eastern region. The availability of regulations and program implementations with adequate budget support will affect the government's performance in fulfilling the right to food.